Determinants of Work Fatigue in Damri Bus Drivers in The Jakarta Metropolitan Area (Jabodetabek) - Basse, Dinda Mariella La; Herbawani, Chahya Kharin; Susanto, Agus Joko; Utari, Dyah (Jurnal Kesmas Jambi, 2025)
Bus drivers are among the occupational groups at high risk of experiencing work-related fatigue, which is a major contributing factor to traffic accidents. This study aims to identify factors associated with work fatigue among urban Damri bus drivers in the Jabodetabek area. A cross-sectional design was used in this study. This study included 98 drivers who met the eligibility criteria. There were two factors that caused fatigue examined in this study, namely internal factors (age, marital status, education level, smoking habits, nutritional status, alcohol consumption, caffeine consumption, and sleep quality) and external factors (mental workload, length of service, working hours, and work stress). Data were collected using standardized instruments: the Swedish Occupational Fatigue Inventory (SOFI) to measure fatigue levels, the Perceived Stress Scale-10 (PSS-10) for work stress, NASA-TLX for mental workload, and the Pittsburgh Sleep Quality Index (PSQI) for sleep quality. Bivariate analysis was conducted using the chi-square test. The results showed that 45.9% of respondents experienced moderate levels of work fatigue. Caffeine consumption (p=0.042) and work stress (p=0.001) were significantly associated with work fatigue. Meanwhile, factors such as age, marital status, education level, nutritional status, alcohol consumption, smoking habits, sleep quality, mental workload, working hours, and years of service were not significantly associated. Caffeine consumption and work stress were key contributors to work fatigue among drivers, while other factors showed no significant association. It is recommended that the company implement stress management programs and regulate caffeine consumption among drivers.